Polymorphisms of genes coding for ghrelin and its receptor in relation to colorectal cancer risk: a two-step gene-wide case-control study - Campa, Daniele; Pardini, Barbara; Naccarati, Alessio; Vodickova, Ludmila; Novotny, Jan; Steinke, Verena; Rahner, Nils; Holinski-Feder, Elke; Morak, Monika; Schackert, Hans K.; Görgens, Heike; Kötting, Judith; et al. (BMC gastroenterology, 2010)
Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor (GHSR), has two major functions: the stimulation of the growth hormone production and the stimulation of food intake. Accumulating evidence also indicates a role of ghrelin in cancer development.